A Comparative Experimental Study on High Strain Rate Response of Graphene-Based Epoxy Nanocomposites - Colak, Ozgen; Bakbak, Okan; Bahlolui, Nadia (WILEY, 2026)
This study investigates the high strain rate behavior of graphene nanoflakes (GNF) and graphene oxide (GO) reinforced epoxy nanocomposites using split Hopkinson pressure bar (SHPB) testing. Nanocomposites were fabricated via solution mixing, and tested under strain rates ranging from approximately 1600-2300/s to evaluate their mechanical response and energy absorption capacity. The incorporation of 0.1 wt% GO resulted in enhanced modulus of elasticity and yield stress, attributed to improved dispersion within the epoxy matrix-similar to the effect observed with GNF at low concentrations. Among formulations, epoxy reinforced with 0.1 wt% GNF exhibited the most significant improvement in mechanical performance, showing the highest maximum stress, post-yield deformation capacity, and energy absorption, with an 18.5% increase compared to neat epoxy at 2300/s. In contrast, increased GO content led to agglomeration and reduced mechanical efficiency. Rate sensitivity was substantially greater in nanocomposites, particularly those with 0.1 wt% GNF and 0.5 wt% GO, compared to neat epoxy. Notably, 0.1 wt% GO addition enhanced rate sensitivity more prominently in the viscoelastic region. These findings suggest that low concentrations of GNF provide the most robust reinforcement for epoxy under dynamic loading, while highlighting the importance of filler dispersion and content in optimizing high strain rate performance.
Keywords: energy absorption; graphene-epoxy; graphene-oxide; high strain rate behavior; MECHANICAL-PROPERTIES; RAMAN-SPECTROSCOPY; THERMAL-PROPERTIES; CARBON NANOTUBES; BEHAVIOR; DISPERSION; GRAPHITE; OXIDE; Engineering; Polymer Science